Antimicrobial Activities Along With Spectrophotometric Assessment of Stability Constants of Copper (II) and Cobalt (II) With 1, 2-Bis(2, 5-dimethoxybenzylidene) Hydrazine. (2nd June 2022) - Fatima, Rida; Nadeem, Sohail; Javed, Mohsin; Iqbal, Shahid; Alsaab, Hashem O.; Awwad, Nasser S.; Ibrahium, Hala A.; Elkaeed, Eslam B.; Alzhrani, Rami M.; Alshehri, Sameer; Ali, H. Elhosiny; Mohyuddin, Ayesha; et al.
Abstract : The stability constants of 1, 2-bis(2, 5-dimethoxybenzylidene) hydrazine (DMBH) were determined using the modified Job's method with the addition of the UV-Vis approach using salts of copper (II) (chloride and acetate) and salts of cobalt (II) (chloride and nitrate). Copper (II) chloride with a ligand at 1L:2M (stoichiometric ratio) was discovered to have a higher stability constant log value (6.995) than other metal salts. The stability constant log value (5.811) for cobalt (II) nitrate at 1L:2M (stoichiometric ratio) was found to be less stable than the other stability constants evaluated. Antimicrobial properties of the ligand were tested against Entamoeba coli, Candida albicans, and Staphylococcus aureus . The ligand was found to be effective against these strains, with positive results.